Environmental Innovation and Firm Performance A Natural Resource-Based View - Salvadó, Javier Amores. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The links between a firm's competitiveness and the natural environment have been studied since the mid 90's. This volume explores, both theoretically and empirically, the relationships between environmental product innovation, green image and firm performance.